The portrayal of women in persuasive advertisement : semiotic analysis of Deeja cosmetic TV commercial - Noor Hanan Mohd Jafar; Hamedi Mohd Adnan; Rosliza Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of advertising is to effectively promote items or services so that people will buy them. Repetition of viewing to the advertisement for the desired product strengthens purchasing habits. However, advertisements frequently contain sexual and objectification of women. This study aims to analyse the ethical decision-making that occurs due to the information presented using the micro and macro text of beauty product commercials. Thus, this study employs a social semiotics model to comprehend emotional strategies and contentious images by examining the process, effects, and consequence of ethical judgment; they function as mechanisms for propagating specific social culture and ethical values. Despite several past research studies attempting to discover beauty products' ideology using social semiotic analysis, no significant progress has been made to explore the studies on local beauty products. Therefore, a semiotic analysis will be used to obtain the data, as it is the most effective way of comprehending how meaning is produced in text. This research exclusively focuses on how Deeja Cosmetic advertisements employ female portrayal and the specific creative strategies the advertisers utilise to persuade and control their customers. From the analysis, women were presented inferiorly relative to their personalities and roles. At the same time, the findings indicate advertisers portray women as an object of desire to persuade the audience for the brand recall.